2014
DOI: 10.1016/j.bbalip.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid regulation of ezrin, radixin, and moesin proteins family: Implications for cell dynamics

Abstract: A key but poorly studied domain of sphingolipid functions encompasses endocytosis, exocytosis, cellular trafficking, and cell movement. Recently, the ezrin, radixin and moesin (ERM) family of proteins emerged as novel potent targets regulated by sphingolipids. ERMs are structural proteins linking the actin cytoskeleton to the plasma membrane, also forming a scaffold for signaling pathways that are used for cell proliferation, migration, and invasion, and cell division. Opposing functions of the bioactive sphin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 149 publications
0
42
0
1
Order By: Relevance
“…The first study that promoted this conceptual shift appeared in the mid-eighties, when sphingosine had been shown to inhibit PKC activity (Hannun et al, 1986). Since then several downstream protein effectors have been described or suggested mainly for sphingosine, ceramide, ceramide-1-phosphate, glycosphingolipids, and sphingosine-1-phosphate (Adada et al, 2014;Arana et al, 2013;Pontier and Schweisguth, 2012).…”
Section: The Sphingolipid Familymentioning
confidence: 99%
“…The first study that promoted this conceptual shift appeared in the mid-eighties, when sphingosine had been shown to inhibit PKC activity (Hannun et al, 1986). Since then several downstream protein effectors have been described or suggested mainly for sphingosine, ceramide, ceramide-1-phosphate, glycosphingolipids, and sphingosine-1-phosphate (Adada et al, 2014;Arana et al, 2013;Pontier and Schweisguth, 2012).…”
Section: The Sphingolipid Familymentioning
confidence: 99%
“…ERM proteins play an important role in cancer migration and invasion and interact with NHE1 protein in migration (27). We speculate that increased NHE1 protein expression may alter its interaction with the ERM complex and promote glioma migration.…”
Section: Direct Interactions Between Nhe1 and Ezrin Are Involved In Gmentioning
confidence: 99%
“…In the present study, we discovered a novel function of the Slp2-a linker domain in the control of ezrin activity. Slp2-a was found to interact via its previously uncharacterized linker domain with PP1b, which is known to inactivate ezrin through dephosphorylation at Thr-567 [21] (Fig. 4), and to recruit PP1b to the plasma membrane of MDCK II cells (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Reports of two recent studies, one demonstrating that both PP1 and PP2 have the ability to dephosphorylate ezrin at threonine 567 [21], and the other showing that PP1 interacts with Slp2-a in vitro [22], prompted us to further investigate the possible involvement of PPs in Slp2-a-mediated ezrin inactivation. Consistent with the results of these previous studies, the results of our coimmunoprecipitation assays in COS-7 cells indicated that all three isoforms of the catalytic subunits of PP1, but neither of the catalytic subunits of PP2s, interacted with Slp2-a (Fig.…”
Section: Slp2-a Interacts With Protein Phosphatasementioning
confidence: 98%